Study on consumer perception towards online ticketing in Malaysia - Nikhashemi, Seyed Rajab; Yasmin, Farzana; Haque, A. K. M. Ahasanul; Khatibi, Ali (2011)
This paper gives a report of a study that investigated peoples‟ perception of online buying tickets (e-ticketing) as well as why some people use this facility while some who do not use it stick to the traditional way to fulfill their needs. In addition, factors such as what inform peoples‟ eagerness and unwillingness to use internet facilities are also examined. The outcome of this research showed a comprehensively integrated framework that can be utilized by policy makers and business enterprises to understand the dynamic relationships among dimensions of perceived risk, user trustworthiness, usefulness, familiarity and confidence. Also, this study considered how price perception and internet security can be utilized to understand the consumers‟ perception. However, further research is needed to examine these factors in Malaysia with additional samples before generalization can be made. Moreover, it is also necessary to review consumers‟ purchasing behavior in making the decision to use the internet as a means of buying online rather than the traditional way.